1997
DOI: 10.1104/pp.113.2.397
|View full text |Cite
|
Sign up to set email alerts
|

A Competitive Enzyme-Linked Immunosorbent Assay to Quantify Acetaldehyde-Protein Adducts That Accumulate in Dry Seeds during Aging

Abstract: A competitive enzyme-linked immunosorbent assay (ELISA) was developed to quantify endogenous acetaldehyde-protein adducts (APAs) produced in plant seeds at low acetaldehyde concentrations without exogenous reducing agents. The key point of this technique is the use of a gelatin-acetaldehyde adduct, which is synthesized under 1 mM acetaldehyde and 10 mM NaCNBH,, to pre-coat plate wells to obtain the proper binding parameters for the quantification of APA in seed proteins. Compared with the traditional, direct E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Acetaldehyde is harmful to cells because of its tendency to form adducts with protein and DNA [15,16]. Cells possess mechanisms to metabolize acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Acetaldehyde is harmful to cells because of its tendency to form adducts with protein and DNA [15,16]. Cells possess mechanisms to metabolize acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation and respiration result in the formation of reactive aldehydes such as malondialdehyde (MDA) and acetaldehyde, which tend to react with proteins and amino acids (Mueller, 1998;Almeras et al, 2003;Weber et al, 2004). Those reactions cause aging and seed damage (Zhang et al, 1995(Zhang et al, , 1997. Until recently, a physiological approach has been taken in research on seed aging, and molecular and genetic studies have been seldom reported (Clerkx et al, 2004a).…”
mentioning
confidence: 99%
“…In the response to cold stress in soybeans, the accumulation of ADH1 and other typical cold response genes was not significant, which was considered to be the reason for poor acclimation capability and cold intolerance (Yamasaki and Randall, 2016). Environmental stresses such as hypoxia (Johnson et al, 1994), drought (Senthil-Kumar et al, 2010), and abscisic acid phytohormone (Zhang et al, 1997) induce a high expression of ADH1 . ADH gene expression, enzyme activity, and related metabolites were analyzed under different temperatures, and the results revealed that the levels of acetaldehyde, ethanol, acetic acid, and ethyl acetate fluctuated at 10°, 20°, and 30°C (Cirilli et al, 2012), suggesting temperature affecting ADH activity and the accumulation of related metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic studies revealed ADH to play a central role in the biosynthesis of an important group of aroma volatiles (C6-derivative compounds) including different aldehydes, alcohols, and esters (Bicsak et al, 1982; Molina et al, 1986; Longhurst et al, 1990; Millán et al, 1990; Speirs et al, 1998). These metabolites are related to fruit flavors, ripening of fruits, antiviral resistance, environmental stresses responses and the ABA phytohormone (Dolferus et al, 1994; Zhang et al, 1997). The ADH1 gene mutant of Chlamydomonas reinhardtii elicits metabolic restructuring during dark anoxic growth (Catalanotti et al, 2012; Magneschi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%